2023
DOI: 10.4018/ijiit.324600
|View full text |Cite
|
Sign up to set email alerts
|

Generating a Mental Health Curve for Monitoring Depression in Real Time by Incorporating Multimodal Feature Analysis Through Social Media Interactions

Abstract: The coronavirus pandemic has led to a dramatic increase in depression cases worldwide. Several people are utilizing social media to share their depression or suicidal thoughts. Thus, the major goal of the proposed study is to examine Twitter posts by users and identify features that may indicate depressed symptoms among online users. A numerical metric for each user is proposed based on the sentiment value of their tweets, and it is demonstrated that this feature can detect depression with good accuracy by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In addition, researchers found individuals with depression, suicidal intent, and schizophrenia exhibiting a pronounced expression of negative emotions compared to healthy controls. This observation is substantiated by various features, including the frequency of negative words [ 20 , 118 , 123 , 204 , 220 ] and negative emoticons [ 130 , 188 ], as well as negative sentiment scores of overall sentences [ 121 ].…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition, researchers found individuals with depression, suicidal intent, and schizophrenia exhibiting a pronounced expression of negative emotions compared to healthy controls. This observation is substantiated by various features, including the frequency of negative words [ 20 , 118 , 123 , 204 , 220 ] and negative emoticons [ 130 , 188 ], as well as negative sentiment scores of overall sentences [ 121 ].…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, Chatterjee et al [ 188 ] uncovered that 56% of suicidal samples demonstrated the association between low agreeableness and high neuroticism scores with increased suicide ideation, compared to most healthy controls with high agreeableness and optimism scores. Another study [ 130 ] also found that individuals with depressive symptoms generally have higher neuroticism and lower optimism scores.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations